2020
DOI: 10.1111/1750-3841.15324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of banana powder (Musa acuminata Colla) on the composition of human fecal microbiota and metabolic output using in vitro fermentation

Abstract: Bananas are rich in indigestible carbohydrates and are considered potential whole‐fruit prebiotics. To investigate banana‐induced changes in the composition of the human gut microbiota and the production of short chain fatty acids (SCFAs), ripe banana (Musa acuminata Colla, Degrees Brix: 22.6 ± 0.2° Bé), from Hainan, China, was powdered and fermented in vitro for 24 hr with the feces of six Chinese donors. The degradation of banana polysaccharides was observed in all six fecal samples. During in vitro fecal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
2
7
0
1
Order By: Relevance
“…These findings are consistent with a previous study that observed similar changes in Proteobacteria and Bacteroidetes abundance after colonic fermentation of banana powder. 38 In Fig. 2E, signifi-…”
Section: Food and Function Papermentioning
confidence: 91%
“…These findings are consistent with a previous study that observed similar changes in Proteobacteria and Bacteroidetes abundance after colonic fermentation of banana powder. 38 In Fig. 2E, signifi-…”
Section: Food and Function Papermentioning
confidence: 91%
“…These facts make banana a good source of prebiotic for Lactobacilli species. Based on the previous research [49], the addition of banana powder to certain species of gut microbiota was capable to regulate the microflora in the intestine and produced different short-chain fatty acids (SCFAs) through in vitro fermentation process after 24 h. Figure 4 demonstrates the chemical structure of the SCFAs produced.…”
Section: Bananamentioning
confidence: 98%
“…Tanin diketahui mampu menghambat pertumbuhan bakteri melalui kemampuannya dalam mendenaturasi protein dan menurunkan tegangan permukaan membran sel, sehingga permeabilitas membran akan meningkat. Selain itu, tannin juga diketahui mampu menghambat produksi enzim bakteri serta menurunkan konsentrasi ion kalium bakteri (Tian et al, 2020).…”
Section: ) Taninunclassified